Extraction of Proteins and Other Intracellular Bioactive Compounds From Baker’s Yeasts by Pulsed Electric Field Treatment - Ganeva, Valentina; Angelova, Boyana; Galutzov, Bojidar; Goltsev, Vasilij; Zhiponova, Miroslava (Frontiers in Bioengineering and Biotechnology, 2020)
Yeasts are rich source of proteins, antioxidants, vitamins, and other bioactive compounds. The main drawback in their utilization as valuable ingredients in functional foods and dietary supplements production is the thick, indigestible cell wall, as well as the high nucleic acid content. In this study, we evaluated the feasibility of pulsed electric field (PEF) treatment as an alternative method for extraction of proteins and other bioactive intracellular compounds from yeasts. Baker’s yeast water suspensions with different concentration (12.5–85 grams dry cell weight per liter) were treated with monopolar rectangular pulses using a continuous flow system. The PEF energy required to achieve irreversible electropermeabilization was significantly reduced with the increase of the biomass concentration. Upon incubation of the permeabilized cells in water, only relatively small intracellular compounds were released. Release of 90% of the free amino acids and low molecular UV absorbing comp, 80% of the glutathione, and ~ 40% of the total phenol content was achieved about 2 h after pulsation and incubation of the suspensions at room temperature. At these conditions, the macromolecules (proteins and nucleic acids) were retained largely inside. Efficient protein release (~ 90% from the total soluble protein) occurred only after dilution and incubation of the permeabilized cells in buffer with pH 8–9. Protein concentrates obtained by ultrafiltration (10 kDa cut off) had lower nucleic acid content (protein/nucleic acid ratio ~ 100/4.5) in comparison with cell lysates obtained by mechanical disintegration. The obtained results allowed to conclude that PEF treatment can be used as an efficient alternative approach for production of yeast extracts with different composition, suitable for application in food, cosmetics and pharmaceutical industries.